A CASE STUDY ON RECENT TRENDS IN GREEN MARKETING IN DEVELOPING ECONOMIES - Sumesh P C (International journal of economic perspectives, 2024)
A commercial strategy known as "green marketing" considers customer concerns about encouraging the preservation and protection of natural resources. In order to safeguard the environment, green marketing campaigns promote the benefits of the firms’ products. The general population quickly realizes that they may unwittingly and unknowingly contribute to greenhouse gases, acid rain, pollution, and the vast accumulation of garbage as they become more educated and informed about environmental concerns. People that care about the environment work to safeguard and restore the resources in our world, and shoppers are more inclined to alter their purchasing patterns in ways that will lessen environmental impact. Hence, green marketing offers a variety of advantages, including access to the global market and a competitive edge. The paper explores how companies are increasingly going for green consumers—those who care about the environment and let it influence their shopping choices. The study’s goal is to understand the potential and difficulties of green marketing. The study also looks at the current trends in green marketing in India. It comes to the conclusion that green marketing will continue to gain popularity among consumers and businesses alike.